Electro-Magnetic Behavior of Highly Correlated Fluorides KFeF3, KCoF3 and KNiF3: A Comparative Ab-initio Study of Cation Effect - Filalli Sihem; Hamdad Noura (Annals of West University of Timisoara: Physics, 2020)
Fluorides-based perovskites are currently the typical materials being used in spintronic devices, optoelectronic and magneto-resistance colossal fields. Solar cells made of Fluoro-perovskite hold much promise for the future of solar energy. The electronic structure and magnetic properties of KFeF3, KCoF3 and KNiF3 Fluorides are studied using ab initio Calculation. We have analysed the structural phases, total and partial electronic densities and band structures within the (DFT) vs the DFT+U description. We show the Electro-Magnetic Behavior using L(S)DA+U vs L(S)DA in a comparative study of cation effect by integrating three types of crystal structures (Cubic (Pm-3m), Four-Layered Hexagonal (P6/mmc), and Orthorhombic (Pnma)). Equilibrium lattices agree very well with experimental and theoretical data. Magnetic moment of each phase is discussed. The obtained results confirmed that the three crystal structures invested here exhibit Ferromagnetic (FM) behavior. The introduction of the Hubbard’s parameter U increases lattice parameters and magnetic moment. We deduce that the second cation plays an important role in the magnetic effects. L(S)DA+U show correctly that KFeF3, KCoF3 and KNiF3 are insulators.